Bridging the library and information science research – practice gap: A panel discussion. Issue 1 (18th October 2019) - Partridge, Helen; Given, Lisa M.; Abdi, Elham Sayyad; Buchanan, George; Bunker, Kate; Luca, Edward; McKay, Dana; Narayan, Bhuva
ABSTRACT: The panel will explore the challenges and opportunities for bridging the library and information science (LIS) research practice gap in Australia. The panel brings together participants from the Research Assistance and Development for Australian Researchers (RADAR) Grant, an initiative of the Library and Information Science Research Australia (LISRA) project. The LISRA project is a three‐year project aimed at encouraging and enabling research culture and practice within the Australian LIS sector.